Knowledge Sharing in Organization: Increasing Job Performance through Absorptive Capacity and Transformational Leadership - Abdullah Maknun Nashir; Sri Astuti Pratminingsih (PT Mattawang Mediatama Solution, 2023)
Currently, organizations across a range of industries actively encourage knowledge sharing to boost employee productivity and organizational competitiveness. However, despite enormous efforts made by organizations to encourage knowledge sharing among their staff, many individuals are hesitant to do so. Therefore, this study attempts to identify the antecedent and consequences of knowledge sharing. This study considers the role of transformational leadership as a contextual factor that acts as moderator in the linkage between absorptive capacity and knowledge sharing. By providing questionnaires to the samples, namely 200 bank employees in Bandung City, West Java Province, a quantitative approach with a survey method is used. Utilizing structural equation modeling (SEM), the data is examined with AMOS software. The results indicate that absorptive capacity has a favorable impact on knowledge sharing, which in turn has a beneficial impact on job performance. Knowledge sharing also acts as a mediator between absorptive capacity and job performance. In addition, absorptive capacity's impact on knowledge sharing is moderated by transformational leadership. This work adds to the body of research on knowledge management in organization by confirming the antecedents and consequences of knowledge sharing aspect, namely absorptive capacity and employee performance.